HUBUNGAN PERILAKU SEHAT SANTRI DENGAN KEJADIAN SCABIES DI PONDOK PESANTREN KABUPATEN LAMONGAN - Ma’rufi, Isa; Istiaji, Erdi; Witcahyo, Eri (FKM - UNEJ, 2012)
Scabies is a common skin disease among the students ofthe boarding school. Scabies is caused by mite infestation as called as Sarcoptes scabiei that can spread easily from human to human, animal to animal or humans to animal sinstead. The purpose of this studyis to measure the prevalence of scabies in students, and to analyzethe relationship between the incidences of scabies by healthy behaviors in students of boarding school at Lamongan, East Java. The type of research is observational and cross-sectional study. Total populationis 59.650 students with a sample ofthe studywere 338 students. The sampling technique on this research was multistage random sampling method. The results showed that 217 students (64.2%) suffered from scabies, and 121 students (35.8%) did not suffer from scabiesor healthy. Based on the statistical test by Chi-square, there is a relationship between the incidence ofscabies by healthy behaviors (p<0.05). It is suggested need for counseling and training on a regular basis about healthy behavior and clean forthe students. Need for cooperation with other agencies, such as Communities Health Center (Puskesmas) in order to prevent and control the incidence of scabiesin students of boarding school.